2002
DOI: 10.1164/rccm.200205-421oc
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Function Tests in Preschool Children with Cystic Fibrosis

Abstract: Pulmonary function tests have rarely been assessed in preschool children with cystic fibrosis (CF). The objective of this multicenter study was to compare pulmonary function in 39 preschool children with CF (height, 90-130 cm; 16 homozygous Delta F508) and in 79 healthy control children. Functional residual capacity (helium dilution technique) and expiratory interrupter resistance (Rint(exp)) (interrupter technique) were measured. As compared with control children, children with CF had significantly higher Rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 29 publications
4
42
0
2
Order By: Relevance
“…Others have described cross-sectional (23)(24)(25)(26)(27) and longitudinal associations (18) between lower lung function and second-hand smoke exposure, but the effect of maternal smoking during pregnancy on lung function in children with CF has not to our knowledge been examined elsewhere. The effect of maternal smoking during pregnancy has been shown to be associated with lower lung function in healthy infants and adolescents and more symptoms in young children with asthma (28)(29)(30).…”
Section: Original Researchmentioning
confidence: 99%
“…Others have described cross-sectional (23)(24)(25)(26)(27) and longitudinal associations (18) between lower lung function and second-hand smoke exposure, but the effect of maternal smoking during pregnancy on lung function in children with CF has not to our knowledge been examined elsewhere. The effect of maternal smoking during pregnancy has been shown to be associated with lower lung function in healthy infants and adolescents and more symptoms in young children with asthma (28)(29)(30).…”
Section: Original Researchmentioning
confidence: 99%
“…4,8 Finally, 3 studies have explored the effects of secondhand smoke exposure in patients with known CFTR genotypes; in 2 studies only participants carrying 2 copies of the most common CF mutation (ΔF508) were analyzed, 4,5 and in the remaining study too few patients were enrolled to examine secondhand smoke interaction with the CFTR genotype. 6 There are no published studies examining whether interactions between modifier genes and secondhand smoke exposure contribute to the variation of CF lung disease.Using data collected by the US Cystic Fibrosis Twin and Sibling Study, we asked the questions: (1) is secondhand smoke exposure associated with worse lung disease and other outcomes in individuals with CF, (2) is there an environment-environment interaction between secondhand smoke exposure and socioeconomic status that correlates with CF lung disease severity, and (3) do gene-environment interactions between the disease-causing gene (CFTR) or the transforming growth factor β1 (TGFβ1) gene influence the effect of secondhand smoke exposure on the pulmonary phenotype? TGFβ1 was selected for study because genotypic variants of TGFβ1 have been shown to modify the severity of CF [11][12][13] and the development and/or severity of other chronic respiratory tract conditions, including asthma 14-18 and chronic obstructive pulmonary disease.…”
mentioning
confidence: 99%
“…4,8 Finally, 3 studies have explored the effects of secondhand smoke exposure in patients with known CFTR genotypes; in 2 studies only participants carrying 2 copies of the most common CF mutation (ΔF508) were analyzed, 4,5 and in the remaining study too few patients were enrolled to examine secondhand smoke interaction with the CFTR genotype. 6 There are no published studies examining whether interactions between modifier genes and secondhand smoke exposure contribute to the variation of CF lung disease.…”
mentioning
confidence: 99%
“…The user-friendliness of the technique and the portability of the equipment, as well as the possibility of a correlation between Rint and spirometric values, have increased the interest in the method and its use in children and adolescents with pulmonary disease. (3,(7)(8)(9)(10)(11)(12)(13)(14) Many patients with CF use bronchodilators to relieve their symptoms or prior to physical therapy, and the measurement of bronchodilator response is an important part of the follow-up of such patients. In studies involving asthma patients, the Rint technique was shown to be accurate in measuring such a response.…”
Section: Introductionmentioning
confidence: 99%